2012
DOI: 10.1016/j.socscimed.2011.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Canaries in a coalmine: Immigration and overweight among Mexican-origin children in the US and Mexico

Abstract: The prevalence of overweight is higher for Hispanic children of immigrants than children of natives. This does not fit the pattern of the epidemiological paradox; the widely supported finding that immigrants tend to be healthier than their U.S.-born peers, and it suggests that exposure to the U.S. increases immigrant children’s risk of overweight. This study’s primary contribution is to better assess how exposure to the U.S. environment affects childhood overweight among a homogamous ethnic group, Mexican-Amer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 50 publications
2
44
0
Order By: Relevance
“…This is especially important in the context of Mexico's obesity epidemic, where migration is emerging as an important vector of change, as ideas and practices related to diet, activity levels, and body size are transmitted between sending and destination communities. Indeed, studies show that immigrants and their children are particularly vulnerable to U.S. norms related to diet and activity (Van Hook et al, 2012), and that children and adults in migrant-sending communities in Mexico are heavier than their counterparts in non-migrant sending communities (Creighton et al, 2011;Riosmena et al, 2013). Our study shows that these impacts extend to the newest members of Mexico's population, placing infants at risk of overweight at the very beginning of their lives.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…This is especially important in the context of Mexico's obesity epidemic, where migration is emerging as an important vector of change, as ideas and practices related to diet, activity levels, and body size are transmitted between sending and destination communities. Indeed, studies show that immigrants and their children are particularly vulnerable to U.S. norms related to diet and activity (Van Hook et al, 2012), and that children and adults in migrant-sending communities in Mexico are heavier than their counterparts in non-migrant sending communities (Creighton et al, 2011;Riosmena et al, 2013). Our study shows that these impacts extend to the newest members of Mexico's population, placing infants at risk of overweight at the very beginning of their lives.…”
Section: Discussionmentioning
confidence: 61%
“…The nutrition transition refers to the shift from locally sourced foods high in fiber and protein to foods sourced from national and international food chains and high in fats and sugars, with increasing rates of overweight as a result. Research shows that Mexican immigrants gain weight with time spent in the U.S., suggesting that practices and ideas related to weight change through exposure to the U.S. food culture and landscape (Antecol and Bedard, 2006;Van Hook et al, 2012). The transmission of these practices and ideas back to Mexico may be one way that migration leads to increased rates of overweight among children and adults in sending communities (Riosmena et al, 2013).…”
Section: Social Remittancesmentioning
confidence: 99%
“…3,4 Besides applying to the health of adults, the immigrant paradox also applies to childhood obesity, with second-and third-generation children from Asia and Latin America having higher levels of obesity than first-generation immigrants. [5][6][7][8] This has led scholars, such as Garcia-Coll and Marks, 9 to ask the question, ''Is becoming American a developmental risk? '' If exposure to and adoption of US lifestyles increases the risk of childhood obesity, one would expect positive relationships between acculturation and obesity in immigrant populations.…”
Section: Introductionmentioning
confidence: 99%
“…It was surprising to find that for both questions, the high acculturated mothers chose higher scores. It has been shown that acculturation is correlated with an increase in BMI (Fuentes-afflick & Hessol, 2008;Liu et al, 2012;Van Hook et al, 2012) so possibly the more acculturated women spend more time with other more acculturated women or may live in neighborhoods with other low Socio Economic Status (SES) white women and may be surrounded by people with a higher BMI. This would explain why they believe other Hispanics in their neighborhood are larger and being around people with a higher BMI has influenced their view on a healthy body size.…”
Section: Objective 2: Maternal Perceptions Of Body Sizementioning
confidence: 99%
“…This could again be due to the increase in BMI that is associated with an increase in acculturation (Fuentes-afflick & Hessol, 2008;Liu et al, 2012;Van Hook et al, 2012). The children in the high acculturated neighborhoods may be larger than the children in the low acculturated neighborhoods.…”
Section: Objective 2: Maternal Perceptions Of Body Sizementioning
confidence: 99%